Tantalum Thin Film Capacitors With Various Types of Counterelectrodes. (1980) - Ferraris, G. P.; May, R.
Abstract : Capacitors have been prepared from N2 -doped, triode sputtered Tantalum films by conventional anodization and photolitographic techniques. NiCr–Au, Ta–Ti–Pd–Au, Ta–NiCr–Pd–Au have been used as counterelectrode materials and the a.c. and d.c. properties of the capacitors have been compared. It has been found that a doped Ta thin layer deposited by sputtering between the dielectric and the top electrode does not negatively affect the capacitors characteristics; moreover, a thermal treatment at temperatures as high as 350℃ can be tolerated. If the Ta film deposited after the dielectric formation is used for resistive elements, a fully compatible R–C process is obtained which requires only two vacuum deposition cycles and four photolithographic steps.